Host genetic background rather than diet-induced gut microbiota shifts of sympatric black-necked crane, common crane and bar-headed goose - Wang, Yeying; Long, Zhengmin; Zhang, Yu; Li, Xianyu; Zhang, Xu; Su, Haijun (Frontiers in Microbiology, 2023)
Gut microbiota of wild birds are affected by many factors, and host genetic background and diet are considered to be two important factors affecting their structure and function. In order to clarify how these two factors influence the gut microbiota, this study selected the sympatric and closely related and similar-sized Black-necked Crane(Grus nigricollis) and Common Crane(Grus grus), as well as the distantly related and significantly different-sized Bar-headed Goose(Anser indicus).The fecal samples identified using sanger sequencing as the above three bird species were subjected to high-throughput sequencing of rbcL gene and 16S rRNA gene to identify the feeding types phytophagous food and gut microbiota. The results showed significant differences in food diversity between black-necked cranes and Common Cranes, but no significant differences in gut microbiota, Potatoes accounted for approximately 50% of their diets. Bar-headed Geese mainly feed on medicinal plants such as Angelica sinensis, Alternanthera philoxeroides, and Ranunculus repens.Black-necked cranes and Common Cranes, which have a high-starch diet, have a similar degree of enrichment in metabolism and synthesis functions, which is significantly different from Bar-headed Geese with a high-fiber diet. The differences in metabolic pathways among the three bird species are driven by food. The feeding of medicinal plants promotes the health of Bar-headed Geese, indicating that food influences the functional pathways of gut microbiota. Spearman analysis showed that there were few gut microbiota related to food, but almost all metabolic pathways were related to food. This indicates that the host genetic background is the dominant factor determining the composition of the microbiota. Monitoring the changes in gut microbiota and feeding types of wild birds through bird feces is of great reference value for the conservation of other endangered species.